Obesity in youth and adults with intellectual disability in Europe and Eurasia. Issue 2 (3rd September 2019) - Sadowsky, Molly; McConkey, Roy; Shellard, Amy
Abstract: Background: Information about obesity among people with intellectual disability comes mostly from small‐scale, national samples in high‐income countries. There are limited data from transnational studies. Method: BMI scores had been obtained for over 25, 000 youth and adults with intellectual disabilities drawn from 60 European and Eurasian countries. Their height and weight had been measured using standardized procedures when they attended Special Olympics Healthy Athletes events. Results: Binary logistic regression identified higher levels of obesity for athletes living in high‐income countries, and for adult females, for those aged 30 years and over, and also for youth aged 8–13 years. Conclusions: Participation in sports does not appear to have protected these athletes from obesity. Arguably, this remains the most pressing health issue for people with intellectual disability, particularly in Western Europe.